The diffuse palmoplantar keratodermas - Hatsell, S... J. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2000)
Diffuse palmoplantar keratodermas belong to a diverse group of skin disorders affecting the palms and soles. These keratodermas manifest as a diffuse thickening of the palmoplantar skin, which can often be associated with other ectodermal disorders. Classification within this group has often been difficult due to the overlapping of phenotypes between disorders and the diversity within one particular disease. During the last few years advances inthe molecular characterization of many of the keratodermas has helped both in distinguishing the different diseases and increasing our understanding of skin biology.
Keywords: Classification; Connexins; Deafness; dermatologija; Desmosomes; Diagnosis; Diagnosis, differential; Epidermis; Esophageal neoplasms; Gap junctions; Hereditary diseases; Keratoderma, palmoplantar, diffuse; kožne bolezni; Molecular biology; Myocardial diseases